Designing Children's Book: Tommy & Darkness to Overcome Fear of Shadows (Ages 6-12) - Darmo, Budi; Sanjaya, Budi; Crysantie, Maylea; Tjiu, Meiliana; Agustino, Matthew (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Children often feel fear of shadows in the dark, which frequently arises from imaginary creatures or their dreams. This fear disrupts their emotional development and affects their sleep routines, leading to issues like insomnia and anxiety. Addressing this issue through effective educational tools such as children's books is crucial, especially in Indonesia where children's interest in reading is still very low. This project aims to create a children's book titled